Acclimation to different depths by the marine angiosperm Posidonia oceanica: transcriptomic and proteomic profiles - Dattolo, Emanuela; Gu, Jenny; Bayer, Philipp E.; Mazzuca, Silvia; Serra, Ilia Anna; Spadafora, Antonia; Bernardo, Letizia; Natali, Lucia; Cavallini, Andrea; Procaccini, Gabriele (Frontiers in Plant Science, 2013)
For seagrasses, seasonal and daily variations in light and temperature represent the mains factors driving their distribution along the bathymetric cline. Changes in these environmental factors, due to climatic and anthropogenic effects, can compromise their survival. In a framework of conservation and restoration, it becomes crucial to improve our knowledge about the physiological plasticity of seagrass species along environmental gradients. Here, we aimed to identify differences in transcriptomic and proteomic profiles, involved in the acclimation along the depth gradient in the seagrass Posidonia oceanica, and to improve the available molecular resources in this species, which is an important requisite for the application of eco-genomic approaches. To do that, from plant growing in the shallow (-5m) and a deep (-25m) portions of a single meadow, (i) we generated two reciprocal EST (Expressed Sequences Tags) libraries using a Suppressive Subtractive Hybridization (SSH) approach, to obtain depth/specific transcriptional profiles, and (ii) we identified proteins differentially expressed, using the highly innovative USIS mass spectrometry methodology, coupled with 1D-SDS electrophoresis and labeling free approach. Mass spectra were searched in the open source Global Proteome Machine (GPM) engine against plant databases and with the X!Tandem algorithm against a local database. Transcriptional analysis showed both quantitative and qualitative differences between depths. EST libraries had only the 3% of transcripts in common. A total of 315 peptides belonging to 64 proteins were identified by mass spectrometry. ATP synthase subunits were among the most abundant proteins in both conditions. Both approaches identified genes and proteins in pathways related to energy metabolism, transport and genetic information processing, that appear o be the most involved in depth acclimation in P. oceanica. Their putative rules in acclimation to depth were discussed.